2022
DOI: 10.1177/23780231221124852
|View full text |Cite
|
Sign up to set email alerts
|

Do Discrimination and Negative Interactions with Family Explain the Relationship between Interracial Relationship Status and Mental Disorder?

Abstract: Using the stress process model, the authors investigate whether individuals in interracial relationships experience greater risk for past-year mood and anxiety disorder compared with their same-race relationship counterparts. The authors also assess interracial relationship status differences in external stressors (i.e., discrimination and negative interactions with family) and whether stress exposure explains mental disorder differences between individuals in interracial versus same-race romantic partnerships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(140 reference statements)
1
0
0
Order By: Relevance
“…Consistent with previous literature (Sosoo et al, 2020;Irby-Shasanmi and Erving, 2022;Majumdar et al, 2022), we found a positive significant association between experiencing discrimination and GAD among university students. Specifically, individuals who have personally been discriminated or had witnessed a relative being discriminated were 4.59 times more likely to have GAD.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous literature (Sosoo et al, 2020;Irby-Shasanmi and Erving, 2022;Majumdar et al, 2022), we found a positive significant association between experiencing discrimination and GAD among university students. Specifically, individuals who have personally been discriminated or had witnessed a relative being discriminated were 4.59 times more likely to have GAD.…”
Section: Discussionsupporting
confidence: 92%
“…The representative and adequate sample allows for meaningfully examining variation in oral health among African American men and women separately [51][52][53]. Third, the data represent one of the most comprehensive social surveys of US-residing people of African descent ever conducted [50,54]. Thus, the data align well with the present foci.…”
Section: Datasupporting
confidence: 55%